ADJECTIVE AS A METHOD OF DEPERSONALIZATION OF MESSAGE: ACTANT-ALTERNATING FUNCTION OF PASSIVE (CLASSICAL APPROACH) - N. V. Solovey; S. D. Isaieva (International Journal of Innovative Technologies in Social Science, 2021)
Semantic perspective of the sentences with passive predication, expressed by the verb in passive voice or using verbal adjectives with passive meaning is analysed in the article. Such types of predication are considered as categorial and non-categorial means of Passive Perspective expression respectively (grammatical and non-grammatical). The general characteristics of the sentences presented by the categorial passive or by non-categorial means are: absence of Agence in grammatical subject position, centripetal direction of the process, expressed by the predicate words and affection of grammatical subject. All these testify the identical character of the expressed relations (by them). Perspective (the direction of the action in the sentence) is defined by subject-object and has the identical nature in both variants.